Associations of vaginal microbiota with the onset, severity, and type of symptoms of genitourinary syndrome of menopause in women - Zeng, Qianru; Shu, Han; Pan, Heng; Zhang, Yonghong; Fan, Ling; Huang, Yubin; Ling, Li (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionGenitourinary syndrome of menopause (GSM) describes the symptoms and signs resulting from the effect of estrogen deficiency on the female genitourinary tract, including genital, urinary, and sexual symptoms. However, besides estrogen deficiency, little is known about the etiology of GSM. The objective of this study was to investigate the effects of vaginal microbiota dysbiosis on the occurrence and development of GSM in perimenopausal and postmenopausal women.MethodsIn total, 96 women were enrolled in this cross-sectional study and clinical data were collected. GSM symptoms were divided into three types: genital, urological, and sexual symptoms. Full-length 16S rRNA gene sequencing using the third-generation PacBio sequencing technology was performed to analyze the vaginal microbiome using vaginal swabs of non-GSM and GSM women with different types of GSM symptoms. Live Lactobacillus Capsule for Vaginal Use (LLCVU) treatment was used to verify the effects of Lactobacillus on GSM symptoms.ResultsWe found that 83.58% (56/67) of women experienced GSM symptoms in the perimenopausal and postmenopausal stages. Among these women with GSM, 23.21% (13/56), 23.21% (13/56), and 53.57% (30/56) had one type, two types, and three types of GSM symptoms, respectively. The richness and diversity of vaginal microbiota gradually increased from reproductive to postmenopausal women. There were significant differences in vaginal microbial community among non-GSM women and GSM women with different types of symptoms. Lactobacillus was found to be negatively associated with the onset, severity, and type of GSM while some bacteria, such as Escherichia-shigella, Anaerococcus, Finegoldia, Enterococcus, Peptoniphilus_harei, and Streptococcus, were found to be positively associated with these aspects of GSM, and these bacteria were especially associated with the types of genital and sexual symptoms in GSM women. LLCVU significantly relieved genital symptoms and improved the sexual life of GSM women in shortterm observation.ConclusionsThe onset, severity, and type of GSM symptoms may be associated with changes in vaginal microbiota in perimenopausal and postmenopausal women. Vaginal microbiota dysbiosis probably contributes to the occurrence and development of GSMsymptoms, especially vaginal and sexual symptoms. Lactobacillus used in the vagina may be a possible option for non-hormonal treatment of GSM women with genital and sexual symptoms.Clinical Trial Registrationhttps://www.chictr.org.cn/indexEN.html, identifier ChiCTR2100044237.